Feedback as a formative tool beyond grading - López Valladares, Carolina; Torres Belma, Alberto (Spanish Journal of Medical Education, 2026)
Feedback is key in education because it helps students improve, self-regulate, and learn meaningfully. It should not be confused with grading, as it involves explaining performance and guiding progress. It should be a continuous, dialogical, and constructive process between teacher and student, promoting reflection, motivation, and autonomy. Its proper application fosters the development of skills and better future professional performance.